Estabelecimento in vitro e propagação de Cordia trichotoma (Vell.) Arrabida ex Steudel (louro-pardo) - Fick, Tiago Antonio (2007)
The Forest Sector has an accomplishment to attend the demand for noble wood products, usually get from native Brazilian species as louro-pardo. Therefore, propagation studies of native species are necessary to produce high quality plants for commercial exploitation and to reduce deforestation pressure over remained populations of native species. The objective of this study was to develop protocols of establishment in vitro and propagation of louro-pardo. Time of seed imbibition and disinfection protocols were studied for in vitro seedling establishment. Seeds were imbibed in distilled and autoclaved water for 0, 24, 48, 72, 96 and 120 h. Seeds were immersed in a sodium hypochlorite solution of 5% for 30 min, submitted to tegument excision and immersed in a alcohol solution of 70% for 30 s. Disinfection was done in sodium hypochlorite solutions of 2 and 5% for 0, 5, 10 15 and 20 min. Seeds without tegument were then inoculated in medium culture for germination. Percentages of disinfection and germination and mean germination time were evaluated. Seedling growth was quantified in 1/2MS and WPM culture mediums. Number of emerged leaves and primary roots and length of shoots and primary roots were evaluated at 7, 14, 21 and 28 days after inoculation. The addition to the WPM culture medium of 0; 0.05; 0.10; 0.15 or 0.20 mg L-1 of 6-benzilaminopurin (BAP), naphthalene acetic acid (NAA) or gibberellic acid (GA3) and the combination of 0 or 0.05 mg L-1 of NAA with 0; 0.10 or 0.20 mg L-1 of GA3 were tested for propagation. At 30 days after inoculation, number of internodes and leaves and plantlet height were evaluated. Plantlets of seminal origin were also excised below or above the first true leaf and the microstumps maintained in vitro with liquid WPM added to the original medium to increase multiplication rate. Number of sprouts and internodes per microstump were evaluated at 21 days after first and second excision. Minicuttings from 2.5 to 4, 4.01 to 5.5 and 5.51 to 7 cm were treated with 0 or 1000 mg L-1 of indol butyric acid (IBA) by basal immersion for 10 s. Survival and rutting percentage and callus formation were evaluated at 60 days after treatment. Imbibition of louro-pardo seeds until 24 hours made easy tegument excision without affecting disinfection and germination. Immersion of seeds with tegument in a sodium hypochlorite solution of 5% for 30 min, tegument excision and immersion in a alcohol solution of 70% for 30 s are enough for an acceptable production of in vitro aseptic seedlings. Louro-pardo seedlings grow satisfactorily in a WPM culture medium without growth regulators. The addition of growth regulators either isolated or combined to the WPM medium did not increase in vitro propagation. Maintaining microstump increased the in vitro multiplication rate in 1.75 fold. Minicuttings of louro-pardo from 2.5 to 5.5 cm showed high survival percentages, but they did not root. Protocols of plantlet acclimatization and clonal propagation by minicuttings should be developed to produce high genetic and physiological quality of louro-pardo plants